Cooperation of Indonesia and China to Escalate Indonesia’s Maritime Infrastructure by Maritime Silk Road in the First Regime of Joko Widodo - Desinta Nur Amanah; Afni Regita Cahyani Muis; Ida Susilowati; Hesti Rokhaniyah (Indonesian Perspective, 2025)
indonesia has a great maritime potentiah, however it is constrained by infrastructure. Then, Indonesia has formed a strategic partnership with China through Belt Road Initiative, which provides funding, technology, technology, and development experience. This cooperation accelerates development, strengthens inter-island connectivity, and enhances global competitiveness. This research employs qualitative methods, including case studies and descriptive analysis based on secondary data. The analysis focuses on two concepts: bilateral economic cooperation in trade, investment, and infrastructure, and the Global Maritime Fulcrum (GMF), which emphasizes the development of maritime infrastructure and connectivity. Indonesia has gained some benefits, such as increased investment in economic sector development and modernization of maritime transport facilities. This cooperation also aligns with President Joko Widodo's vision to make Indonesia a global maritime hub through port development, maritime connectivity, and national maritime industry.